Wisata Religi sebagai Strategi Branding Kampung Adat Jalawastu - Widyaningrum, Septiana Yustika; Turyati, Turyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Jalawastu Traditional Village in Brebes Regency is a tourism village that represents the acculturation of local indigenous traditions and Islamic values. This study aims to examine religious tourism as a destination branding strategy for Jalawastu Traditional Village by emphasizing the integration of culture, spirituality, and a community-based tourism (CBT) approach. The research employs a qualitative methodology through field observations, interviews with traditional leaders, documentation, and a literature review. Data were analyzed thematically to identify branding practices, community involvement, and the roles of stakeholders in sustainable tourism development. The findings indicate that religious tourism branding in Jalawastu Traditional Village is constructed through the integration of cultural and spiritual elements reflected in the Ngasa Traditional Ceremony, the Perang Centong ritual, the uniformity of traditional house architecture, the symbolism of white attire, and collective prayer practices. The CBT approach positions the indigenous community as the primary actor in cultural preservation and tourism management, while local government and educational institutions serve as facilitators of empowerment and capacity building, including digital marketing training. In addition, the utilization of conventional and digital media, such as documentary films and online promotional platforms, has proven effective in expanding branding outreach and strengthening tourism experiences grounded in cultural and spiritual narratives. This study concludes that religious tourism functions not only as a destination promotion strategy but also as a mechanism for preserving the cultural and spiritual identity of indigenous communities.